Environmental Assessment of Lightweight Electric Vehicles - Egede, Patricia (Sustainable Production, Life Cycle Engineering and Management,, 2017)
This monograph adresses the challenge of the environmental assessment of leightweight electric vehicles. It poses the question whether the use of lightweight materials in electric vehicles can reduce the vehicles' environmental impact and compares the environmental performance of a lightweight electric vehicle (LEV) to other types of vehicles. The topical approach focuses on methods from life cycle assessment (LCA), and the book concludes with a comprehensive concept on the environmental assessment of LEVs. The target audience primarily comprises LCA practitioners from research institutes and industry, but it may also be beneficial for graduate students specializing in the field of environmental assessment.